Analisa Perbandingan Metode Certainty Factor dan Teorema Bayes Untuk Mendiagnosa Penyakit Asam Urat - Widia Ningsih; Nelly Astuti Hasibuan; Edizal Hatmi (STMIK Budi Darma, 2022)
Gout is a disease that often occurs around us, but many are not aware of the symptoms of the disease and how to detect it, one way to diagnose is using an expert system, in the process of diagnosing using methods, there are many methods to determine the accuracy of the results of the diagnosis One of the methods used is the certainty factor and the Bayes theorem, so many are confused about which method to use to carry out the diagnosis process. So we need a process of comparing methods with the intention of knowing which method is more effective, with a fast and precise calculation process so as to present better and more accurate results, the comparison process will apply the exponential comparison method by assessing the level of processing difficulty, processing time, and probability results so that it can be known which method is right for the diagnostic process. Based on the results of the comparison using the exponential comparison method, the certainty factor method gets a result of 14 while the Bayes theorem method gets 3. By looking at the value of this comparison, it can be said that the certainty factor method is the right method for diagnosing gout.